Determinants of Community Interest in Batang Toru District Using Cicil Gold Products at PT. Bank Sharia Mandiri Kcp Batang Toru - ika purnama; nofinawati nofinawati; sarmiana batubara; ferri alfadri (Institut Agama Islam Negeri Padangsidimpuan, 2021)
The lack of interest of the people of Batang Toru District in using gold installment products. The increase in gold prices makes some people tend to want to own gold. This causes people's interest to own gold to also increase. Gold installment products attract people's attention to own gold. However, what happened to the people of Batang Toru Subdistrict they felt burdened with the down payment given by the bank to the community, which was 20%, so that the community preferred to pay in installments for gold in a conventional way compared to sharia. The purpose of this study is to determine whether promotion, price, and service quality affect the interest of the people of Batang Toru District using gold installment products at PT. Bank Syariah Mandiri KCP Batang Toru. The theory used in this research is public interest, promotion theory, price, service quality. This study is a quantitative study using multiple regression analysis, data collection techniques using a questionnaire with a sample of 100 people in Batang Toru District. The sampling technique is incidental sampling. Data processing was carried out with SPSS version 23. The results of the analysis carried out by researchers, the results of the partial study (t test) showed that promotion had an effect on the interest of the people of Batang Toru District using gold installment products at PT. Bank Syariah Mandiri KCP Batang Toru. Price has an effect on the interest of the people of Batang Toru District using gold installment products at PT. Bank Syariah Mandiri KCP Batang Toru. And the quality of service has an effect on the interest of the people of Batang Toru District using gold installment products at PT. Bank Syariah Mandiri KCP Batang Toru. Judging by the promotion F test, price and quality of service have a simultaneous effect on the interest of the people of Batang Toru District using gold installment products at PT. Bank Syariah Mandiri KCP Batang Toru.